Effective biocontrol efficacy of Bacillus subtilis CV21 against cherry leaf spot disease caused by Alternaria phytopathogens and growth promotion of flowering cherry (Prunus sargentii Rehder) seedlings - Vantha Choub; Eun-Young Yim; Su-In Choi; Sang-Jae Won; Jae-Hyun Moon; Ju-Yeol Yun; Henry B. Ajuna; Young Sang Ahn (Biological Control)
Cherry leaf spot (CLS) disease is one of the most common and deleterious disease of flowering cherry seedlings which lowers frost tolerance, growth, and biomass production during the season, and reduces flower production in following season. This study isolated two phytopathogens, Alternaria alternata CH3 and Alternaria alternata CH10, and confirmed their pathogenicity of CLS disease in flowering cherry seedlings, causing brownish spots and necrotic lesions on the leaves. We also isolated a plant growth-promoting bacteria (PGPB), Bacillus subtilis strain CV21, and investigated its antifungal and plant growth-promoting properties. The bacterium produced cell wall-degrading enzymes such as chitinase, β-1,3-glucanase, and protease and effectively antagonized both A. alternata CH3 and A. alternata CH10 and the crude enzyme fraction (100 µl/mL) of B. subtilis CV21 inhibited spore germination by 40.1 % and 25.1 % and reduced mycelial growth by 29.1 % and 42.5 % against A. alternata CH3 and A. alternata CH10. The crude enzyme fraction degraded the cell walls of both phytopathogens in a concentration-dependent manner, causing swelling with bulbous structures in the hyphal cell, and cell wall lysis with severe perforations, loss of shape and aggregation of spores compared to control. Treatment with the bacterial culture broth on flowering cherry seedlings reduced CLS disease by 1.3-fold and 3.4-fold compared to the chemical treatment and the control group, respectively. In addition, B. subtilis CV21 also demonstrated plant growth-promoting properties such as indole-3-acetic acid (IAA) production up to a maximum concentration of 3.5 µg/mL during the experimental period and exhibited potential for phosphate solubilization and nitrogen fixation. The inoculation of nursery seedlings with B. subtilis CV21 culture broth improved the chlorophyll content, and increased seedling growth and biomass production compared to chemical treatment and the control group. The results demonstrate that the B. subtilis CV21 could be effectively applied as a bio-fungicide to control CLS and as bio-stimulant/bio-fertilizer to enhance the growth of flowering cherry seedlings.